Evaluation of Three Influenza Neuraminidase Inhibition Assays for Use in a Public Health Laboratory Setting during the 2011–2012 Influenza Season. (September 2013) - Murtaugh, William; Mahaman, Lalla; Healey, Benjamin; Peters, Heather; Anderson, Barbara; Tran, Mandy; Ziese, Marci; Carlos, Maria Paz
Objectives: We evaluated the implementation of three commericially available neuraminidase inhibition assays in a public health laboratory (PHL) setting. We also described the drug susceptibility patterns of human influenza A and B circulating in Maryland during the 2011–2012 influenza season. Methods: From January to May 2012, 169 influenza virus isolates were tested for phenotypic susceptibility to oseltamivir, zanamivir, and peramivir using NA-Fluor™, NA-Star®, and NA-XTD™ concurrently. A 50% neuraminidase inhibitory concentration (IC50 ) value was calculated to determine drug susceptibility. We used the standard deviation based on the median absolute deviation of the median analysis to determine the potential for reduced drug susceptibility. We evaluated each assay for the use of resources in high- and low-volume testing scenarios. Results: One of the 25 2009 influenza A (H1N1) pandemic isolates tested was resistant to oseltamivir and peramivir, and sensitive to zanamivir, on all three platforms. Eighty-two influenza A (H3N2) and 62 B isolates were sensitive to all three drugs in all three assays. For a low-volume scenario, NA-Star and NA-XTD took 120 minutes to complete, while NA-Fluor required 300 minutes to complete. The lowest relative cost favored NA-Star. In a high-volume scenario, NA-Fluor had the highest throughput. Reagent use was most efficient when maximizing throughput. Cost efficiency from low- to high-volume testing improved the most for NA-Star. Conclusions: Our evaluation showed that both chemiluminescent and fluorescent neuraminidase inhibition assays can be successfully implemented in a PHL setting to screen circulating influenza strains for neuraminidase inhibitor resistance. For improved PHL influenza surveillance, it may be essential to develop guidelines for phenotypic drug-resistance testing that take into consideration a PHL's workload and available resources.